Boerhavia diffusa L. ethanol extract suppresses inflammatory responses via inhibition of Src/Syk/TRAF6. (August 2015) - Thai, Ha Van; Kim, Eunji; Kim, Seung Cheol; Jeong, Deok; Yang, Sungjae; Baek, Kwang-Soo; Kim, Yong; Ratan, Zubair Ahmed; Yoon, Kee Dong; Kim, Jong-Hoon; Cho, Jae Youl
Highlights: Ethanol extract ameliorates gastritis symptoms. Ethanol extract and its ingredient luteolin inhibit release of NO and TNF-α. Ethanol extract and its ingredient luteolin suppress NF-κB and AP-1 activation. Ethanol extract targets Syk, Src, and TRAF6. Abstract: Boerhavia diffusa L. is a green vegetable used as an herbal medicine in several Asian countries for the treatment of hepatitis, kidney stones, liver disorders, nephritis, urinary disorders, and urinary retention. In this study, the anti-inflammatory activity and the molecular inhibitory mechanisms of B. diffusa L. ethanol extract (Bd-EE) in vitro and in vivo were evaluated. Lipopolysaccharide (LPS)-activated peritoneal macrophage RAW264.7 cells and a mouse gastritis model induced by HCl/EtOH treatment were chosen to determine the in vitro and in vivo anti-inflammatory activities of Bd-EE. This extract (100 and 200 µg/ml) significantly ( P < 0.01) inhibited nitric oxide (NO) and tumour necrosis factor (TNF)-α production in peritoneal macrophages and in RAW264.7 cells during LPS exposure at both. The inducible nitric oxide synthase (iNOS) and TNF-α mRNA expression levels were decreased. In addition, nuclear levels of p65, p50, c-Fos, and c-Jun transcription factors were reduced by Bd-EE treatment; moreover, it inhibited NF-κB upstream signalling via IκBα, PI3K, Syk, and Src. Furthermore, analysis of AP-1 upstream signalling revealed that the AP-1 activation pathway consisting of TRAF6, TAK1, MKK4/7, and MKK3/6 was also predominantly inhibited by Bd-EE. By HPLC analysis, luteolin was identified as a major ingredient displaying NO inhibitory activity. The data provided here strongly suggest that the anti-inflammatory property of Bd-EE is linked to the suppression of Syk, Src, and TRAF6.